Fakhruddin Al-Razi’s concept of Place - الضاهر سليمان; صافي علي; كالو أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Knowing the reality and essence of the place was difficult for all philosophers and speech scholars, due to too many questions about this concept and a lack of acomprehensive definition of it. However, we find that there are indications for some of them that exceed those of others with the intuition of the mind and this is what we find it with Fakhruddin Al-Razi. He is considered to be one of the later Ash’arites, who disclosed evidences that surpassed the evidences of his predecessors. In this research, we will deal with the specificity of Al-Razi’s stand on the problem of the place in the introduction and then present some questions about this concept. As for the elements of the research, they included views and opinions regarding the topic, followed by what the essence of the place and its reality are at Al-Razi’s thought, and then indicating the evidences of those saying that the place is not the distance and refuting their views And their arguments by Al-Fakhur Al-Razi then presenting the concept of emptiness inside and outside the world. In conclusion, we concluded that Al-Fakhur Al-Razi was one of those who proved the concepts of space and emptiness, despite his hesitation in the beginnings and in the end his decisive opinion, which he determined, was taken from Plato as the dimension and the space.